2002
DOI: 10.1034/j.1399-3054.2002.1140214.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of putrescine accumulation in tobacco transgenic plants with different expression levels of oat arginine decarboxylase

Abstract: Arginine decarboxylase (ADC; EC 4.1.1.19) is a key enzyme in one of the two possible ways to synthesize putrescine (Put) in plants. In previous work (Masgrau et al. 1997), we observed an altered phenotype (growth inhibition, leaf chlorosis and necrosis) in tobacco transgenic plants (Nicotiana tabacum L. var. Wisconsin-38) containing the oat ADC cDNA under the control of a tetracycline inducible promoter, the severity of which was correlated with Put content. Now we have analysed the T2 generation of a selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 32 publications
(75 reference statements)
2
21
0
3
Order By: Relevance
“…In the present experiment, Ni increased the Put level and markedly decreased Spd and Spm levels, and these changes were accompanied by the substantial generation of ROS. Although some experiments have shown that Put has the ability to scavenge ROS in vitro (Sharma and Dietz 2006), it should be noted that a mass accumulation of Put is generally considered toxic to plants and eventually leads to apoptotic cell death if its level becomes too high (Panicot et al 2002;Takao et al 2006). It has often been suggested that Put and derived PAs (Spd, Spm) may have distinct functions in response to stress.…”
Section: Discussionmentioning
confidence: 98%
“…In the present experiment, Ni increased the Put level and markedly decreased Spd and Spm levels, and these changes were accompanied by the substantial generation of ROS. Although some experiments have shown that Put has the ability to scavenge ROS in vitro (Sharma and Dietz 2006), it should be noted that a mass accumulation of Put is generally considered toxic to plants and eventually leads to apoptotic cell death if its level becomes too high (Panicot et al 2002;Takao et al 2006). It has often been suggested that Put and derived PAs (Spd, Spm) may have distinct functions in response to stress.…”
Section: Discussionmentioning
confidence: 98%
“…This raises the possibility that embryonic arrest in the double mutant is associated with toxicity of overaccumulated putrescine. Previous studies have shown that overexpression of oat ADC in tobacco leads to abnormal phenotypes such as short internodes, thin stems and leaves, leaf necrosis, and reduced root growth, the severity of which is correlated with putrescine content (Masgrau et al, 1997;Panicot et al, 2002a). In contrast, Noury et al (2000) generated transgenic rice plants that show normal growth but up to a 10-fold increase in the amount of putrescine in the seeds compared to that in wild-type seeds by overexpressing the oat ADC cDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in adc tobacco and rice transgenic plants (Burtin and Michael 1997;Capell et al 2004) and in rice (Roy and Wu 2001), tobacco (Franceschetti et al 2004), Arabidopsis (Kasukabe et al 2004) and sweet potato (Kasukabe et al 2006) transgenic plants over-expressing other PA biosynthetic genes, samdc and Spd synthase. However, morphological abnormalities such as short internodes and wrinkled leaves have been reported in transgenic tobacco plants over-expressing odc (DeScenzo and Minocha 1993; Kumria and Rajam 2002), adc (Masgrau et al 1997;Panicot et al 2002) and samdc (Noh and Minocha 1994;Waie and Rajam 2003) genes. Our results and the published work indicate that the phenotypic abnormalities in transgenic plants over-expressing PA genes might depend upon the transgene expression and cellular of PA levels.…”
Section: Transformation and Regenerationmentioning
confidence: 99%